2012
DOI: 10.1308/003588412x13171221499865
|View full text |Cite
|
Sign up to set email alerts
|

The STAR score: a method for auditing clinical records

Abstract: INTRODUCTIONAdequate medical note keeping is critical in delivering high quality healthcare. However, there are few robust tools available for the auditing of notes. The aim of this paper was to describe the design, validation and implementation of a novel scoring tool to objectively assess surgical notes.METHODSAn initial ‘path finding’ study was performed to evaluate the quality of note keeping using the CRABEL scoring tool. The findings prompted the development of the Surgical Tool for Auditing Records (STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…Tuffaha et al produced a similar scoring system based on the CRABEL score [ 13 ]. This scoring system (STAR score) also takes into account the quality of the consenting process and operation note.…”
Section: Discussionmentioning
confidence: 99%
“…Tuffaha et al produced a similar scoring system based on the CRABEL score [ 13 ]. This scoring system (STAR score) also takes into account the quality of the consenting process and operation note.…”
Section: Discussionmentioning
confidence: 99%
“…This review showed that the use of a pro forma improves the quality of clerking documentation in elective surgical patients, and that standardisation of the medical record improved the quality of patient care. [6][7][8][9][10][11][12][13][14][15] Evidence is presented across the audits that the use of a pro forma leads to significantly improved documentation for surgical patients, in areas such as previous medical history and medication history. [7,12,13,15] It has also been shown to significantly improve the completion of VTE assessment.…”
Section: Designmentioning
confidence: 99%
“…So for example in performing falls risk assessments, or in reducing harder end points like hospital acquired pressure ulcers. An example of such an evaluation is the previously quoted work by Tuffaha et al [12].…”
Section: E Future Poc Application Development and Researchmentioning
confidence: 99%
“…Historically, many clinical audit [10], [11] processes-designed to collect information about an organizations or individuals compliance with clinical quality standards (eg -care measures to prevent pressure ulcers)-have been centered around primary data collection on paper-based structured, or unstructured, assessment tools. An example is the Surgical Tool for Auditing records (STAR), used for auditing clinical records in the UK [12].…”
Section: Introductionmentioning
confidence: 99%